Analysis and Business Development Strategy Agroindustry Herbal - Fatmawati; Moh. Kurdi (Agricultural Science, 2018)
One of the herbs that are very potential to be developed in the village of Matanair, Rubaru District, Sumenep Regency is instant herbal medicine. Immediate herbal medicine is an effort to make it easier for consumers to enjoy herbal medicine. Formulation of the problem in this study How is the feasibility of an instant herbal agroindustry business in Sumenep Regency. As well as how to develop the next herbal medicine agro-business business in Sumenep Regency. The analysis used in this study to see the feasibility of the company used financial feasibility analysis. Market analysis is carried out by analyzing the development of demand (demand side) and supply side (instant side) for several years to come. Furthermore, to see the development prospects and strategies used a SWOT analysis. Based on the results of the study, the following conclusions were obtained: On the results of the calculation of the feasibility analysis that has been done is got the NPV value of Rp. 241.604,291.70, -; Pay Back Period with a period of 1.53 years; IRR value is 58.80%, and Net B / C is 2.35. Alternative strategies that can be applied to herbal medicine agro-industries based on business positions in quadrant I, namely SO STRATEGY, in the SO strategy four alternative strategies can be used, including market penetration, attention to production continuity, expanding product distribution, carrying out missions product introduction outside Madura.